Oscar Niemeyer: diálogos con lo natural (2019)
The modern architecture of Brazil has been incorporating from the end of the thirties several concepts of the European Modern Movement, but, without doing it in a direct way but reinterpreting, translating and adapting to the specific climatic and landscape conditions of the coun-try. This text describes the appropriation of the new theories from the analysis of some model projects in which the concatenation between spatiality, natural landscape and landscaping appears forceful. The works, made by multidisciplinary teams guided by master Niemeyer, demonstrate how the new Brazilian spatiality arises from the fusion be-tween architectural, artistic, natural and structural elements, with the use of similar morphological rules in different aspects of the projects, as happens for example in the Pampulha church, where architects, art-ists, engineers and landscapers -Oscar Niemeyer, Candido Portinari, Joaquim Cardoso and Roberto Burle Marx- operate in communion, applying aesthetic criteria of a similar nature. The Brazilian revolution is the assimilation of a working method based on the dialogue between masters of different knowledges, in which the architect has the impor-tant role of "orchestrator" and as an objective the holistic construction of a new modern, tropical and integrated landscape.